Selected Parameters of Nutritional and Pro-Health Value in the Common Carp (Cyprinus carpio L.) Muscle Tissue - J. Kłobukowski; K. Skibniewska; K. Janowicz; F. Kłobukowski; E. Siemianowska; E. Terech-Majewska; J. Szarek (Journal of Food Quality)
This study analysed the effect of the type of production on the nutritional and health value of common carp muscle tissue, especially lipid-related indexes. The muscle tissue of common carps originating from three types of fish farms with different technological levels (i.e., intensive, low-intensive, and semiextensive) was studied. The type of production technology, especially the intensive breeding technique, has been shown to have a significant effect on dry weight, total protein, and total fat content in the common carp muscle tissue under study. The muscles of fish originating from these farms were characterised by the highest values of the mentioned indicators, which amounted to 24.6%, 18.74%, and 1.58%, respectively, for dry matter, protein content, and total fat content. The type of feed used in intensive, low-intensive, and semiextensive common carp breeding has been proven to have a highly significant effect on the fatty acid profile. As regards unsaturated fatty acids, monounsaturated fatty acids were dominant in all cases. The muscle tissue of fish cultured in farms with a semiextensive technological level was characterised by the highest content of unsaturated fatty acids. Moreover, the ratio of polyunsaturated fatty acids to saturated fatty acids was, in this case, the most favourable. Dietary indices of atherogenicity (AI) and thrombogenicity (TI) were studied as well. In all analysed cases, the values of these indices were very favourable and several times lower than for other animal fats.